What do higher education instructors consider useful regarding student ratings of instruction? Limitations and recommendations - Safavi, Seyedeh Azadeh; Abu Bakar, Kamariah; Ahmad Tarmizi, Rohani; Alwi, Nor Hayati (Elsevier, 2012)
Instructional improvement is a main purpose of performing Student Ratings of Instruction (SRI) in higher education. Although issues on the subject of student ratings have been extensively researched, there have been limited studies dealing with the question that what types of ratings information are useful for instructors in order to make improvements in their instructional practices? This study explored the utility of ratings information as perceived by instructors, examined significant differences in utility of ratings information based on instructors’ characteristics, and identified instructors’ reactions and recommendations. The population comprised 1139 instructors from 15 faculties of a major Malaysian research university. 330 of them were surveyed, with a response rate of 75.1%. The responses were subjected to descriptive statistics, principal component analysis, one-way ANOVA, and independent t-test. The results showed that the ratings information which focused on instructor's efforts in student learning enhancement was considered useful for instructional improvement. The instructors acknowledged that there were limitations in the current student ratings being used. They shared the views that faculties/departments should not limit themselves to the common set of rating items, and that instructors with teaching problems should be recommended to use of instructional consultant services.